Conceptual Model of Lean Sustainable Supply Chain for The Footwear Industry - Surjasa, Dadang Surjasa; Wahyuda, Wahyuda; Marie, Iveline Anne Marie (JURNAL TEKNIK INDUSTRI, 2025)
Companies are adapting to the era of globalization, striving to remain competitive amid global pressures such as climate change and consumers who are increasingly critical of sustainability issues. The footwear industry has several factors that affect the environment, such as short product life cycles, high demand volatility, and many manufacturing process failure risks. Forty different materials used in the footwear manufacturing process, such as textiles, synthetics, leather, EVA, rubber, and TPU, impact sustainability. This study creates a conceptual model for designing a Lean Sustainable Supply Chain and Quality Risk Management model. The concept of lean and sustainability is the basic foundation for the footwear industry to be more competitive. Furthermore, the research uses the DMAIC (Define, Measure, Analyze, Improve, Control) approach from Six Sigma to integrate the lean sustainability method in the supply chain to increase the efficiency of the footwear industry. A case study was conducted on the footwear industry in the city of Serang. The research results are a conceptual model to increase process efficiency and improve quality in the Sustainable Supply Chain network. This Model improves quality by reducing variations, reducing the risk of failure, and creating a sustainable supply chain network by integrating DMAIC and Lean sustainable supply chain in the footwear industry.